Hypervitaminosis D in the pediatric population - Pawłowski, Bartosz; Maliszewska, Bernadeta; Łaba, Łukasz; Łuczyński, Dominik; Tokarzewska, Agata; Żybowska-Męczyńska, Monika; Kłusek , Magdalena; Klimas, Filip; Rusiński, Kacper; Sienkiewicz, Michał (Quality in Sport, 2025)
Vitamin D is a fat-soluble vitamin that plays a huge role in the metabolism of bones and teeth, which is especially important among pediatric patients. Its deficiency in the developmental period is associated with a decrease in bone mass, bone mineralization disorders, as well as the development of rickets. In addition, vitamin D has an immunomodulatory effect, and its reduced level correlates with a higher incidence of certain autoimmune diseases and cancer. However, it is worth noting that nowadays, in the era of high availability of over-the-counter (OTC) drugs and dietary supplements, not only hypovitaminosis D can be dangerous and pose a significant clinical problem. More and more parents decide to administer exogenous vitamin D preparations, often without prior consultation with a doctor to determine the optimal dose or duration of supplementation. Unfortunately, it happens that over-the-counter supplements contain a higher dose of vitamin D than the manufacturer suggests. This is very often due to inadequate control of supplement production. Restrictions similar to those in the case of drug production should be sought. It should be remembered that the human body, thanks to exposure to sunlight, under the influence of UV radiation, is able to synthesize endogenous vitamin D on its own. Another source of vitamin D is many foods such as fatty fish, eggs, mushrooms or dairy products, which should be in the diet of every person, especially a child. Therefore, it becomes necessary to define uniform recommendations for doctors and parents regarding vitamin D supplementation in children, as well as to educate the public about possible toxic effects resulting from excessive supply.